(untitled) (Bangladesh Journal of Botany, 2019)
Five media were formulated with 0% (control, T1), 25% (T2), 50% (T3), 75% (T4) and 100% (T5) inclusion of low-cost muriate of potash (MOP)-potassium (K) replacing high-cost reagent K2SO4-K and Spirulina platensis was cultured for 18 days. Cell dry weight, optical cell density and chlorophyll-a content of S. platensis cultured in five treatments were registered at every three-day interval and economic performance was calculated to observe the effect of K2SO4-K replacement with MOP-K. The cell biomass production and chlorophyll-a content of S. platensis cultured in 25 and 50% use of MOP-K instead of K2SO4-K (T2 and T3) did not represent any significant difference with the control treatment of 100% K2SO4-K (T1). However, further addition of MOP-K in T4 and T5 significantly reduced the cell growth and pigment content of S. platensis. In addition, a significant reduction of production cost was calculated as more percentage of K2SO4- K was replaced with MOP-K.